Perancangan User Interface pada Startup Woodmaker dengan Menggunakan Metode Design Thinking - Chintya Devi Pratiwi; Helmy Syakh Alam; I Gede Juliana Eka Putra; A.A. Istri Paramitha (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2025)
In today's digital era, the use of websites is one of the right choices to make it easier for business people who will sell their goods or products to reach a wider range. With a design that is arranged in such a way and attractively, it will make it easier for prospective customers to get the goods they want. Before building a website, it is certainly very important for the author to determine the website user interface, to ensure that the website can be in accordance with the needs that customers want. In this study, the Design Thinking method will be used in the process of creating the Woodmaker website user interface display. Therefore, the researcher conducted a study entitled "User Interface Design on the WoodMaker startup using the Design Thinking Method" to make it easier for prospective customers to get price information, product details and of course make it easier for customers in the process of ordering craft goods. With this method, the author hopes to provide solutions to the problems faced by customers and craftsmen in the form of website interface designs made by the author using user interface design tools, namely Figma.